2017
DOI: 10.22159/ijpps.2017v9i2.16204
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anticancer Activity of Methanolic Extract From Stephania Elegans

Abstract: Objective: The present work was aimed to investigate the in vitro antioxidant and anti-cancer activities of methanolic extract of Stephania elegans, an unexplored species from Menispermaceae family. Methods:The methanolic extract of S. elegans tubers was prepared and phytochemical screening and total phenolic content were analyzed by using standard methods. In vitro, antioxidant potential of methanolic extract was determined by 2-2'-azinobis (3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS) and ferric reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…The controls have all the reaction reagents excluding the sample. The absorbance was measured at 750 nm and compared to gallic acid equivalent (GAE) after 30 min of incubation at 37°C [13].…”
Section: Determination Of Total Polyphenol Contentmentioning
confidence: 99%
“…The controls have all the reaction reagents excluding the sample. The absorbance was measured at 750 nm and compared to gallic acid equivalent (GAE) after 30 min of incubation at 37°C [13].…”
Section: Determination Of Total Polyphenol Contentmentioning
confidence: 99%
“…Antioxidant nature of plant-based compounds plays a significant role in controlling many ailments including the dreadful cancer [54][55][56]. Vitamin C, a known antioxidant, exerts its effects both through acting as antioxidant and through non-antioxidant effect.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study through MTT assay, IC 50 of Datura metel leaf and stem extract was evaluated against Vero and MCF7 cell line [19]. In another study, IC 50 of Stephania elegans on MCF7 was reported to be 158.7 ± 0.13 µg/ml [20].…”
Section: Anticancer Assaysmentioning
confidence: 99%